Novel homogeneous selective electrocatalysts for CO2 reduction: an electrochemical and computational study of cyclopentadienyl-phenylendiamino-cobalt complexes. Issue 11 (16th September 2020) - Melis, Nicola; Mocci, Francesca; Vacca, Annalisa; Pilia, Luca
Abstract : Cobalt cyclopentadienyl phenylendiamine complexes are revealed to be efficient and selective electrocatalysts for CO2 reduction, resulting in a 31-fold catalytic current without the hydrogen evolution. Abstract : Four cyclopentadienyl-phenylendiamino-cobalt complexes [CoCp(bqdi)] with different substituents ( R ) at the phenylene moiety (bqdi, I ; o -perfluoro-bqdi, II ; p -NO2 -bqdi, III ; p -COOH-bqdi, IV ) have been studied with an aim to investigate their capability as catalysts for the CO2 reduction. These compounds were characterized by cyclic voltammetry measurements both under nitrogen and CO2 atmospheres, showing an increase in the cathodic current ranging from 3.36 (III ) to 5.59 times (II ) that of the measurement under nitrogen. Moreover, with the addition of water, the current enhancement in the presence of CO2 reaches 31.07 times that of the case of complex II . Interestingly, these complexes exhibit very good selectivity toward CO2 reduction irrespective of hydrogen even in the presence of water. The relative turnover frequencies were also estimated, given the values ranging from 3.23 (III ) to 187.21 s −1 (II ) in the presence of water. In addition, these results were analysed by means of density functional theory (DFT) calculations and Fukui functions analysis. In particular, DFT results clearly show effects of different substituents on the electrochemical properties of these compounds. Whereas, the Fukui functions analysis indicates that the most favourable positions for an electrophilic attack on the reduced complex are the nitrogen and cobalt atoms.